(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study investigates the concept of liminality in connection to gender restrictions in Joseph Conrad’s Lord Jim, contending that the novel creates transitory spaces both physical and psychological that shake up fixed concepts of identity, notably masculinity. The study, which draws on liminality and gender performativity theories, investigates how Jim’s repeated moral failures and narrative fragmentation leave him in a situation that is neither wholly heroic nor entirely condemned. Simultaneously, the erasure or silencing of female voices in the book parallels larger patriarchal patterns found in colonial literature. Using a critical gender lens, this study illustrates how Lord Jim problematizes stable gender categories and reflects the larger worries of identity creation within imperial and existential contexts. However, he encounters failure and loses everything; eventually, he sacrifices himself and chooses death to avenge his fallen men. Jim experiences several liminal and in-between-ess spaces throughout the novel as a dreamer, field-mate, lord, dishonoured, leader, husband, and self-sacrificing hero.